2015
DOI: 10.1159/000369073
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aquaporin-1, Aquaporin-3, and Aquaporin-5 Correlates with Nodal Metastasis in Colon Cancer

Abstract: Objectives: The clinical significance of aquaporin-1 (AQP1), aquaporin-3 (AQP3), and aquaporin-5 (AQP5) expression was analyzed in a large number of patients with colon cancer. Methods: AQP1, AQP3, and AQP5 expression was investigated based on the immunohistochemistry of tissue microarray specimens from 486 colon cancer patients who underwent curative surgery. Scores were given to the staining intensity and percentage of positive cells, and the staining score was defined as the sum of these scores then used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 22 publications
5
61
0
1
Order By: Relevance
“…On the contrary, the highest AQP3 expression levels were found in poorly differentiated tumors that are usually more aggressive and later stages of the disease. Since tumorigenesis of PDA occurs in ductal epithelial cells and in moderately differentiated tumors a positive correlation was found between AQP5 and Ki‐67, one of the most important markers of active cellular proliferation, this indicates that AQP5 may play an important role in PDA progression and proliferation, as reported for other types of cancer and depicted in our proposed model (Fig. ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…On the contrary, the highest AQP3 expression levels were found in poorly differentiated tumors that are usually more aggressive and later stages of the disease. Since tumorigenesis of PDA occurs in ductal epithelial cells and in moderately differentiated tumors a positive correlation was found between AQP5 and Ki‐67, one of the most important markers of active cellular proliferation, this indicates that AQP5 may play an important role in PDA progression and proliferation, as reported for other types of cancer and depicted in our proposed model (Fig. ).…”
Section: Discussionsupporting
confidence: 78%
“…Recently, an increasing number of reports showed that AQP3 and AQP5 are abundantly expressed in different tumors such as squamous cell carcinoma of the skin, colon cancer, breast cancer, lung cancer, ovarian cancer, cervical cancer, and prostate cancer, playing key roles in cell proliferation and migration . In tumors, cells divide more frequently, thus needing more energy to maintain their rapid growth.…”
Section: Introductionmentioning
confidence: 99%
“…Although AQP3 has not been identified as a monogenic cause of IBD, patients with ulcerative colitis have significantly lower expression of epithelial AQP3 during both inflammation and clinical remission (17). Conversely, AQP3 expression is highly increased in many colon carcinomas and is correlated with metastatic spread (37). As shown here, AQP3-dependent H 2 O 2 cellular entry increases colonic epithelial migration, and it is plausible that AQP3-facilliated H 2 O 2 transport may play a role in the development of colonic cancers and metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of colon cancer, Moon and colleagues showed expression of AQP1 in colonic adenoma, primary and secondary colon cancer, but not in normal colonic mucosa, suggesting a role of AQP1 in the early stage of colon cancer tumorigenesis [19]. Additionally, its expression was reported to be associated with clinical characteristics known to be prognostic such as histological grade and status of lympho-vascular invasion and nodal involvement [18,22,23,27,28,29,30]. These findings suggested the link between AQP1 and cancer biological functions, which act to drive cancer development and progression.…”
Section: Aquaporinmentioning
confidence: 99%